«Essi sono le stelle de’ campi». Note su una lista di fiori tra le carte di Federico Borromeo (Carte Romanze, 2020)
The passion for plants, floral collecting and gardening are phenomena with a European diffusion in the seventeenth century. Among the papers by Federico Borromeo there are various testimonies of botanical interest, including an unpublished list of flowers, on which this article focuses. This list is of historical and linguistic interest because it preserves a pre-Linnean botanical nomenclature. This nomenclature is investigated with reference to the sector treaties, the botanical lexicography of the eighteenth and nineteenth centuries and other handwritten documents of the XVIIth century showing that Italian was used as the language of international communication among botanists, floriculturists and collectors of the time.
Keywords: seventeenth century; botany; botanical language; Federico Borromeo